2015
DOI: 10.1016/j.neucom.2014.09.068
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the role of fixational eye movements in real-world scenes

Abstract: Cite this article as: Andrés Olmedo-Payá, Antonio Martínez-Álvarez, Sergio Cuenca-Asensi, J.M. Ferrández, E. Fernández, Modeling the role of fixational eye movements in real-world scenes, Neurocomputing, http://dx.doi.org/10.1016/j. neucom. 2014.09.068 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Lorach et al (2012) demonstrated the feasibility to reconstruct the spatiotemporal properties of several ganglion cell groups with the visual inputs from an asynchronous contrast sensor, which supposedly provides improved temporal precision compared to the conventional frame-based image inputs. More recently, incorporating the involuntary eye movements (microsaccades, drifts and tremor) in the retina models was shown to improve the visual sensitivity to temporal and spatial changes in luminance (Olmedo-Payá et al, 2015). This type of retina encoder conceptualized a retinotopic input-output transformation, but it was far from a cell-specific strategy.…”
Section: Stimulation Encodingmentioning
confidence: 99%
“…Lorach et al (2012) demonstrated the feasibility to reconstruct the spatiotemporal properties of several ganglion cell groups with the visual inputs from an asynchronous contrast sensor, which supposedly provides improved temporal precision compared to the conventional frame-based image inputs. More recently, incorporating the involuntary eye movements (microsaccades, drifts and tremor) in the retina models was shown to improve the visual sensitivity to temporal and spatial changes in luminance (Olmedo-Payá et al, 2015). This type of retina encoder conceptualized a retinotopic input-output transformation, but it was far from a cell-specific strategy.…”
Section: Stimulation Encodingmentioning
confidence: 99%
“…In this framework some authors are starting to incorporate these involuntary eye movements into their retinal models using different strategies: micro-saccades, drifts and tremor. The results show that transforming an originally stationary image into one that varies spatiotemporally (thus mimicking real fixational eye movements) improve feature estimation (Martínez-Álvarez et al, 2013;Olmedo-Paya et al, 2015).…”
Section: Delivering Of Information To Implantsmentioning
confidence: 94%